Decoding Appropriate English for Flight Attendant Learning Materials for Gen Z Students: Insights and Preferences - Putu Ayu Kinanti Praditha; Putu Kerti Nitiasih; I Gede Budasi; I Ketut Trika Adi Ana (Jurnal Pendidikan Bahasa Inggris undiksha, 2024)
Currently students are still studying to become flight attendants, they cannot provide valid data. Therefore, further investigation is urgently needed to systematically identify and assess English learning materials tailored for aspiring Gen Z flight attendants. This research analyzes appropriate English learning resources designed for Gen Z students who aspire to pursue a career as a flight attendant. Using a needs analysis approach, this research follows the target situation analysis model. This research was conducted at a private aviation school in Bali. Data collection methods are interviews and questionnaires, with sample selection guided by purposive sampling. Using an interactive data analysis model, qualitative analysis is applied to analyze the collected data. The research results show that, according to curriculum requirements, learning materials must facilitate effective communication skills that are useful and important for the role of flight attendants in the world of work. The senior flight attendant emphasized the importance of the material in increasing students' self-confidence and fostering a friendly attitude in using English, as well as understanding how to communicate with passengers in a good and purposeful manner. Students also prefer varied content such as multimedia, such as video examples and online quizzes. This study emphasizes adapting English learning materials for Gen Z flight attendant candidates to facilitate good, friendly, confident English communication. And by increasing cross-cultural understanding and providing interesting digital resources that can be accessed via smartphone according to developments in this century.